Annual Plan 2004-2005(Volume-II) National Capital Territory of Delhi - Planning Commission (Planning Commission, 2004)
Education holds the key to economic growth, social transformation, modernization and national integration. Plan proposals of Delhi have been formulated keeping is view the broad objectives laid down in the National Policy on General Education. Earnest efforts are being made by the Govt, of N.C.T. of Delhi to provide educational facilities to every child. While improving the educational facilities quantitatively, adequate attention is also paid to improve the quality of Education. The main emphasis in the 9th Plan 1997-2002 was to make education a vehicle to enhance the capabilities of the young generation of Delhi with special emphasis on mass-literacy, non-formal education, improvement of quality of education and vocational education.
Planning Department Government of National Capital Territory of Delhi